Rheomicroscopy of Starch Gelatinisation (Annual Transactions of the Nordic Rheology Society, 2024)
Rheomicroscopy offers simultaneous monitoring of microstructure through microscopy and rheology, in large deformation and small deformation oscillating shear as well as in compression. The method was used to visualise and explain starch gelatinisation and how it is affected by shear, granule architecture and botanical origin. Shear had a strong influence on paste viscosity and was explained by granule disruption following swelling. Gelatinisation occurred during narrower temperature range for potato starch than for maize starch, which in turn both had a different behaviour from wheat starch. A-type wheat starch was also shown to have different gelatinisation behaviour than B-type wheat starch.